Implementation of Sharia Marketing Strategy as a Solution to Increase Linkaja Syariah Consumer Loyalty - Firdausi, Firna Nahwa; Ardyansyah, Farid (Universitas Alma Ata, 2023)
The purpose of this research is to find out the sharia marketing strategy as a solution to increase LinkAja Syariah consumer loyalty. The method used is a qualitative approach with descriptive analysis. Source of data obtained from primary data through interviews. The findings of this study indicate that the sharia marketing strategy implemented by LinkAja is a strategy that can increase the loyalty of LinkAja Syariah consumers. Promos and events are one of the sharia marketing strategies that are organized by providing various features in one application that make it easy and very practical for users to carry out all their transaction needs. The LinkAja Syariah strategy is carried out as an implementation to the community of the importance of sharia-based transaction education. The sharia marketing strategy is a form of activity that aims to meet customer needs through good behavior in providing halal products and services following a mutual agreement to achieve material and spiritual balance.